Pengaruh Pengungkapan Corporate Social Responsibility (CSR), Ukuran Perusahaan, dan Profitabilitas Terhadap Nilai Perusahaan Pada PT ANTAM Tbk - Irwandi, Miladatul Husni; Lubis, Nasrul Kahfi; Murni, Mayang (Journal Research of Economic and Bussiness, 2025)
This study aims to determine the effect of Corporate Social Responsibility (CSR) Disclosure, Firm Size, and Profitability on Firm Value at PT. Antam Tbk. The type of data in this study uses quantitative data with the population in this study being PT Antam Tbk. The sampling technique uses the saturated sampling method. The data collection method comes from the company's historical data, namely financial data that has been audited by the company PT. Antam Tbk which is listed on the IDX in the period 2009-2023. The data analysis method used in this study is multiple linear regression analysis by operating SPSS (Statistical Package for the Social Science) Software. The results of this study indicate that the Corporate Social Responsibility (CSR) disclosure variable has a positive and significant effect on firm value at PT. Antam Tbk, the firm size variable has a positive and significant effect on firm value at PT. Antam Tbk, the profitability variable has a positive and significant effect on rirm value at PT. Antam Tbk, simultaneously Corporate Social Responsibility (CSR) disclosure, firm size, and profitability have a significant effect on firm value at PT. Antam Tbk. Keywords: Corporate Social Responsibility (CSR) Disclosure, Firm Size, Profitability, Firm Value